2015
DOI: 10.1021/acs.jafc.5b02891
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Comparison of Soy Isoflavone Extracts in Human Plasma

Abstract: The soy isoflavones daidzein and genistein produce several biological activities related to health benefits. A number of isoflavone extracts are commercially available, but there is little information concerning the specific isoflavone content of these products or differences in their bioavailability and pharmacokinetics. This study describes the development and validation of an analytical method to detect and quantify daidzein, genistein, and equol in human plasma using liquid chromatography coupled to tandem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…Some studies have described that genistein presented higher bioavailability than daidzein , while others reported the contrary . In some studies, no differences in bioavailability were observed between daidzein and genistein .…”
Section: Discussionmentioning
confidence: 92%
“…Some studies have described that genistein presented higher bioavailability than daidzein , while others reported the contrary . In some studies, no differences in bioavailability were observed between daidzein and genistein .…”
Section: Discussionmentioning
confidence: 92%
“…Whole soy and its constituent daidzein have a positive effect on renal function in a clinical trial [ 7 ]. Pharmacokinetics of daidzein in human, mouse, and rat demonstrates its presence as glucuronides [ 13 , 14 ]. Comparative pharmacokinetics of traditional Chinese medicine Nao Mai Tong in a rat study also demonstrates the presence of daidzein [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately, no estrogenic effects on the endometrium or vagina were reported in these studies with up to 2 years of use. The poor bioavailability of genistein and daidzein from soy may explain the variable and relatively modest if any effects on menopausal symptoms ( Yang et al, 2012 ; Rodriguez-Morato et al, 2015 ).…”
Section: Botanicals Used By Menopausal Womenmentioning
confidence: 99%